Sosialisasi Sadar Wisata Sebagai Upaya Pengembangan Desa Wisata Berbasis Masyarakat di Desa Fatukoto - Nugraha, Yudha Eka (Jurnal ABDIMAS PARIWISATA, 2021)
Socialization of Tourism Awareness as an Effort to Develop Community-Based Rural Tourism in Fatukoto Village. Rural Tourism Development is a government program to build a village tourism system and improve community welfare. In 2019, the Ministry of Tourism collaborates with universities to build tourist villages in East Nusa Tenggara Province. One of the villages is Fatukoto Village as a pilot rural tourism that has natural potential in the form of Pine Forest, Kaenka Lake, and Fatunausus Marble Cliffs. This community service seeks to increase tourism awareness for the people of Fatukoto Village through the SAPTA PESONA approach. The method chosen in implementing this community service is community education in which there are observations, interviews, documentation, focus group discussions, and socialization. The number of participants who took part in this service activity was 30 people aged 17-50 years. The result of this community service is the formation of a tourism awareness group in Fatukoto Village and a tourism work program in Fatukoto Village such as plans for cultural activities, regulations on the cleanliness of tourist attractions, and commitment to building Fatukoto tourism villages.